2018
DOI: 10.12669/pjms.343.14345
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high-intensity laser therapy and combination of transcutaneous nerve stimulation and ultrasound treatment in patients with chronic lumbar radiculopathy: A randomized single-blind study

Abstract: Objective:To compare the effects of high-intensity laser therapy (HILT) and a combination of transcutaneous nerve stimulation (TENS) with ultrasound (US) therapy on pain and functionality in patients with chronic lumbar radiculopathy.Methods:This prospective randomized comparative study was conducted in Department of physical medicine and rehabilitation, Turgut Ozal Medicine Center, Malatya, Turkey from April 2016 to September 2016. A total of 54 patients with chronic lumbar radiculopathy were enrolled in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 19 publications
0
24
1
1
Order By: Relevance
“…In the first group of classification (HILT and exercise) 4 studies 14,32,34,35 were about spinal pain which were matched to another group. [16][17][18]20 The average of the effect size differences was higher in the first group (1/08) for spinal pain patients. In contrast, the effect size in second group of studies was higher for knee pain patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the first group of classification (HILT and exercise) 4 studies 14,32,34,35 were about spinal pain which were matched to another group. [16][17][18]20 The average of the effect size differences was higher in the first group (1/08) for spinal pain patients. In contrast, the effect size in second group of studies was higher for knee pain patients.…”
Section: Discussionmentioning
confidence: 93%
“…3,[15][16][17][18][19] Bjordal et al showed that the overall effects of lowpower laser therapy and anti-inflammatory drugs cointerventions, were poorer than those studies without these co-interventions. 20 On the other hand, Santuzzi et al found that the combined treatment of low-level laser therapy and cyclooxygenase-2 may have better effects on wound closure and scar organization. 21 As there are increasing data available regarding the effects of HILT in musculoskeletal injuries, this study was designed to evaluate the literature assessing the influence of adding interventions to HILT on musculoskeletal pain management.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent single-blind RCT by Kolu et al (24) compared the effects of HILT and a combination of transcutaneous nerve stimulation (TENS) with ultrasound therapy (UST) on pain intensity (VAS) and functional status (ODI) in 54 patients with lumbar pain caused by chronic radiculopathy. The patients were randomly divided into two groups: the first group (n=27; received 10 sessions of a combination of hot-pack, TENS, UST, and isometric lumbar exercises) and the second group (n=27; received hot-pack, isometric lumbar exercises, and HILT: 25 Hz, 10 W with 12 J/cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, it does not correspond to functional improvement in the recovery of postural control and stability. Our team will certainly continue to research laser irradiation protocols because it is worth expanding the methodology to use adequate objective measurement tools (e.g., Biodex isokinetic system, surface electromyography device, or goniometry pendulum test) (24) and increase the sample size in specific groups. We did not provide the COP analysis for each leg separately.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Boyraz et al did not find this difference between two methods for the treatment of pain in patients with lumbar disc protrusion 27 and Kolu et al showed a greater therapeutic effect for physiotherapy than HILT in the treatment of radiculopathy. 28 One reason for these controversies is probably the differences between study populations and the disorders which have been assessed.…”
Section: Introductionmentioning
confidence: 99%